Caring and coping: the dementia caregivers - Efstathiou, Georgios; Tsangari, Haritini; Karayiannis, George; Papastavrou, Evridiki (My University, 2011)
Objectives: Caring for a family member with Alzheimer's disease is associated with increased burden and depression. Effective coping with the hardships and demands of caring may help to sustain the caregiver and lessen the effect of the stressors. The objective of this study was to examine caregivers’ coping styles and the relationship with reported levels of burden and depression. Method: A cross-sectional correlation study was employed. One hundred and seventy-two caregivers of patients suffering from Alzheimer's type dementia participated in the study. All patients were recruited from neurology clinics. The Greek versions of four measuring instruments used were: the Memory and Behaviour Problem Checklist, the Burden Interview, the Centre for Epidemiological studies-Depression scale and the Ways of Coping Questionnaire. Results: Positive coping is negatively correlated with burden (r = −0.20) and wishful thinking strategies were related positively (r = 0.16). The relation between depression and positive coping strategies is highly significant (p < 0.01), whereas for burden the relation is significant (p < 0.05). Regression analyses showed that positive coping strategies are the most powerful, both in terms of predicting depression levels, and also in terms of moderating the effect of burden on depression. Conclusion: Positive coping approaches need to be developed by caregivers so as to continue their caring role
Keywords: Alzheimer's; Burden; Caregiver; Caring; Coping